Encountering enchantment: stories from the street football court in Singapore. (17th November 2017) - Teo, Shaun S. K.; Neo, Harvey
Abstract: While enchantment has been used productively to think through the geographies of social encounter, extant research – drawing largely from cases in the West – has reinforced a celebratory notion of enchantment, characterized by egalitarianism and serendipity. In this paper we draw ethnographically on encounters between Malay and Chinese users of two street football courts in Singapore, a non-Western context where principles of public interaction converge with but also exceed those in the West. In so doing we aim to advance existing debates by conceptualizing enchantment as it is negotiated and constituted, rather than asking if observed occurrences live up to dominant interpretations. We find that enchantment can be experienced through the construction, perpetuation and negotiation of boundaries; it is also a product of enduring rhythms in space that are produced and developed via the interactions of its users over time. In specifying the different ways in which enchantment is created, negotiated and lived we contribute to signalling the validity of expansive notions of publicness i.e. the different ways in which encounter in public space can be made meaningful and fulfilling.